Resistance to Antimicrobial Peptides in Vibrios - Delphine Destoumieux-Garzón; Marylise Duperthuy; Audrey Sophie Vanhove; Paulina Schmitt; Sun Nyunt Wai (MDPI AG, 2014)
Vibrios are associated with a broad diversity of hosts that produce antimicrobial peptides (AMPs) as part of their defense against microbial infections. In particular, vibrios colonize epithelia, which function as protective barriers and express AMPs as a first line of chemical defense against pathogens. Recent studies have shown they can also colonize phagocytes, key components of the animal immune system. Phagocytes infiltrate infected tissues and use AMPs to kill the phagocytosed microorganisms intracellularly, or deliver their antimicrobial content extracellularly to circumvent tissue infection. We review here the mechanisms by which vibrios have evolved the capacity to evade or resist the potent antimicrobial defenses of the immune cells or tissues they colonize. Among their strategies to resist killing by AMPs, primarily vibrios use membrane remodeling mechanisms. In particular, some highly resistant strains substitute hexaacylated Lipid A with a diglycine residue to reduce their negative surface charge, thereby lowering their electrostatic interactions with cationic AMPs. As a response to envelope stress, which can be induced by membrane-active agents including AMPs, vibrios also release outer membrane vesicles to create a protective membranous shield that traps extracellular AMPs and prevents interaction of the peptides with their own membranes. Finally, once AMPs have breached the bacterial membrane barriers, vibrios use RND efflux pumps, similar to those of other species, to transport AMPs out of their cytoplasmic space.